Clinical Characteristics of Methanol-Induced Optic Neuropathy: Correlation between Aetiology and Clinical Findings. (9th November 2022) - Sun, Qiao; Sun, Mingming; Zhang, Yuan; Wang, Song; Bai, Wenhao; Wei, Shihui; Xu, Quangang; Zhou, Huanfen
Abstract : Purpose . To show the clinical characteristics, identify the magnetic resonance imaging (MRI) and optical coherence tomography (OCT) features, and observe the visual outcome of methanol-induced optic neuropathy. Methods . Clinical data were retrospectively collected from in-patients diagnosed with methanol-induced optic neuropathy in the Neuro-Ophthalmology Department of the Chinese People's Liberation Army General Hospital from January 2016 to January 2021. Results . Eight patients were included in this study. The exposure time was 6–34 h for ingestion, 3-4 months for inhalation, and more than ten years for skin absorption. All patients demonstrated bilateral acute visual impairment. Seven of eight patients had other accompanying systemic symptoms. Seven of eight patients demonstrated optic nerve lesions in MRI, and five presented with a hyperintense T2 signal in a "central" type. OCT showed the macular ganglion cell layer and inner plexiform layer (mGCL-IPL) thinning before the peripapillary retinal nerve fiber layer (pRNFL) thinning. The visual improvement was achieved transiently for seven of eight patients after treatment. One patient with a mitochondrial DNA mutation maintained a bilateral no-light perception (NLP) from the onset to the last visit. All patients had poor visual prognoses, with either light perception or NLP. Conclusions . Methanol-induced optic neuropathy is a rare bilateral optic neuropathy with a poor visual outcome. A centrally hyperintense T2 signal of the optic nerve is common in methanol-induced optic neuropathy. The thinning of the mGCL-IPL is more sensitive than that of the pRNFL for early diagnosis. A mitochondrial genetic defect may be a predisposing factor for methanol-induced optic neuropathy.